The Role of Sugar Signaling in Regulating Plant Fatty Acid Synthesis - Zhai, Zhiyang; Keereetaweep, Jantana; Liu, Hui; Xu, Changcheng; Shanklin, John (Frontiers in Plant Science, 2021)
Photosynthates such as glucose, sucrose and some of their derivatives play dual roles as metabolic intermediates and signaling molecules that influence plant cell metabolism. Such sugars provide substrates for de novo fatty acid biosynthesis. However, compared with the well-defined examples of sugar signaling in starch and anthocyanin synthesis, until recently relatively little was known about the role of signaling in regulating fatty acid and lipid biosynthesis. Recent research progress shows that trehalose 6-phosphate and 2-oxoglutarate play direct signaling roles in the regulation of fatty acid biosynthesis by modulating transcription factor stability and enzymatic activities involved in fatty acid biosynthesis. Specifically, mechanistic links between SnRK1 mediated T6P sensing and its regulation by phosphorylation of WRI1 stability, DGAT1 enzyme activity, and of 2-OG-mediated relief of inhibition of ACCase activity by protein PII are exemplified in detail in this review.